Truth, Correspondence, And Pragmatism Theories In Management - Dewita; Amalia Afsari; Elsa Manora Nasution; Miss Diana Laewang; Siti Mujiatun (Aksaqila International Humanities and Social Sciences [AIHSS] Journal, 2025)
Philosophy of science as a basis for understanding theories of truth related to management. This research covers four main theories of truth: correspondence, coherence, pragmatism, and religion. Correspondence theory prioritizes congruence between statements and objective facts, while coherence theory judges truth based on the interrelationships between statements. Pragmatism establishes truth based on its practical value, while religious theory regards truth as an absolute value that comes from God.This study uses the literature review method, analyzing relevant sources to investigate the concept of truth in philosophy of science and its relation to management science. The research findings show that these theories of truth provide important insights into the decision-making process and managerial practice. Through a pragmatic approach, management becomes more elastic, outcome-focused, and responsive to changes in the environment.The paper concludes that truth theories provide a strong conceptual basis for developing efficient, relevant, and sustainable management principles. Suggestions are provided to expand the study of the relevance of truth theories in the context of contemporary management and their implementation in organizations.